Edukasi Pengelolaan Air Bersih Kepada Masyarakat di Desa Temon Grobogan - Mika Agustiana; Christina Nur Widayati; Anita Lufianti; Yuwanti; Fitriani; Yesita Ragil Kusumaningrum; Rahmawati (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: Clean water management is very important in human life. Water is a necessity for every living creature, without water there would be no life. Objective: This community service aims to provide education on clean water management to the people of Temon Grobogan Village. Method: This community service uses lecture and discussion methods. Results: The results of this community service showed that there was an increase in community knowledge about clean water management before and after education. Conclusion: Clean water management education can increase public knowledge.